Quantification of AMPA receptor subunits and RNA editing-related proteins in the J20 mouse model of Alzheimer’s disease by capillary western blotting - Milham, Luke T.; Morris, Gary P.; Konen, Lyndsey M.; Rentsch, Peggy; Avgan, Nesli; Vissel, Bryce (Frontiers in Molecular Neuroscience, 2024)
Accurate modelling of molecular changes in Alzheimer's disease (AD) dementia is crucial for understanding the mechanisms driving neuronal pathology and for developing treatments. Synaptic dysfunction has long been implicated as a mechanism underpinning memory dysfunction in AD and is thought to result in part from changes in adenosine deaminase acting on RNA (ADAR) mediated RNA editing of GluA2 subunit of AMPA receptors and changes in AMPA receptor function at the post synaptic cleft, but few studies have investigated changes in the relevant proteins. Notably, the few AD studies that focus on studying changes in protein expression rather than changes in the mRNA, often use inefficient and inaccurate techniques. Here we demonstrate the value of automated capillary western blotting to investigate changes in protein expression of AMPA receptor subunits (GluA1-4) the ADAR RNA editing proteins (ADAR1-3) and proteins known to regulate RNA editing (PIN1, WWP2, FXR1 and CREB1) in the J20 AD mouse model. We describe extensive optimisation and validation of the automated capillary western blotting method, demonstrating the ideal approach in the use of common housekeeping proteins for normalising protein load, in addition to characterising the optimal protein/antibody concentrations to ensure accurate protein quantification. Following this, we assessed changes in proteins of interest in 44-week-old J20 AD mice hippocampus and found increased expression of ADAR1 p110 and GluA3 and a decrease in ADAR2. These changes signify a shift in the balance of proteins that play a critical role at the synapse. Regression analysis revealed unique J20specific correlations between changes in AMPA receptor subunits, ADAR enzymes, and proteins that regulate ADAR stability in J20 mice, highlighting potential mechanisms mediating RNA-editing changes found in AD. We discuss how our findings in the J20 mice generally reflect changes seen in the human AD brain. This study underlines the continual need for the application of novel techniques, like automated capillary western blotting, to unravel the molecular complexities of AD.